Surface Electrical Stimulation for Treating Swallowing Disorders after Stroke: A Review of the Stimulation Intensity Levels and the Electrode Placements. (2nd April 2014) - Poorjavad, Marziyeh; Talebian Moghadam, Saeed; Nakhostin Ansari, Noureddin; Daemi, Mostafa
Abstract : Neuromuscular electrical stimulation (NMES) for treating dysphagia is a relatively new therapeutic method. There is a paucity of evidence about the use of NMES in patients with dysphagia caused by stroke. The present review aimed to introduce and discuss studies that have evaluated the efficacy of this method amongst dysphagic patients following stroke with emphasis on the intensity of stimulation (sensory or motor level) and the method of electrode placement on the neck. The majority of the reviewed studies describe some positive effects of the NMES on the neck musculature in the swallowing performance of poststroke dysphagic patients, especially when the intensity of the stimulus is adjusted at the sensory level or when the motor electrical stimulation is applied on the infrahyoid muscles during swallowing.